Chandler Bing's Sarcasm in the TV Series Friends: A Pragmatic Analysis - Sembodo, Thomas Joko Priyo; Wijana, I Dewa Putu; Munandar, Aris (Lexicon, 2025)
This study investigates the use of sarcasm by the character Chandler Bing in the American sitcom Friends, focusing on Seasons 1 through 3. Through a pragmatic lens, the analysis identified 134 sarcastic utterances and classified them based on the Gricean conversational maxims they flout as well as the communicative functions they serve. The findings reveal that the maxim of quality is the most frequently violated, with 91% of sarcastic utterances exhibiting a deliberate contrast between literal meaning and intended implication. Additionally, sarcastic functions are grouped into three categories: negative evaluation, positive evaluation, and other purposes. While no utterances were found to express positive evaluation, 36% delivered negative assessments of the hearer, and 64% fulfilled other functions, such as teasing, expressing frustration, or asserting social bonds. The study underscores the complexity of sarcasm as a pragmatic phenomenon and highlights its central role in character development and humor in scripted media. Limitations include the use of a single source and broad functional categories, which future research may refine by incorporating more diverse datasets and nuanced classifications.